The effects of background music on English reading comprehension for English foreign language learners: evidence from an eye movement study - Su, Yankui; He, Meiling; Li, Rongbao (Frontiers in Psychology, 2023)
Based on previous literature, the present study examines the effects of background music on English reading comprehension using eye tracking techniques. All the participants, whose first language was Chinese, were selected from a foreign language college and all of them were sophomores who majored in English. The experiment in this study was a 2 (music tempo: fast and slow) × 2 (text difficulty: difficult and easy) × 2 (background music preference: high and low) mixed design. Both musical tempo and English reading passage were within-subjects factors, and the level of music listening preference was a between-subjects factor. The results showed that the main effect of the music tempo was statistically significant, which indicated that participants read texts more quickly in the fast-tempo music condition than in the slow-tempo music condition. Furthermore, the main effect of the text difficulty was statistically significant. Additionally, the interaction between the text difficulty and music tempo was statistically significant. The music tempo had a greater effect on easy texts than on difficult texts. The results of this study reveal that it is beneficial for people who have a stronger preference for music listening to conduct English reading tasks with fast-tempo music. It is detrimental for people who have little preference for background music listening to complete difficult English reading tasks with slow-tempo music.